Foreword (Signifiances (Signifying), 2017)
The aim of the electronic journal Signifiances (Signifying) with an international review committee is to disseminate works on language that takes care of deal with the human factor with all the repercussions it generates: corporality, social and ecological inscriptions, the importance of movement in learning processes learning, in the apprehension or in the production of language. « Language and enaction » therefore appeared to be the most relevant thematics for a publication in this inaugural volume, with a double issue.